Quantification of myelinated endings and mechanoreceptors in human digital skin - Nolano, Maria; Provitera, Vincenzo; Crisci, Claudio; Stancanelli, Annamaria; Wendelschafer-Crabb, Gwen; Kennedy, William Robert; Santoro, Lucio (Annals of neurology, 2003)
We used immunohistochemistry and confocal microscopy applied to fingertip punch biopsy to study glabrous skin innervation in 14 healthy subjects. In addition to epidermal nerve fibers, we quantified mechanoreceptors and their myelinated afferents. Using digital images and dedicated software, we calculated caliber, internodal and nodal length, and G‐ratio of the last four internodes of the myelinated endings. In our skin samples, we found a mean density of 59.0 ± 29.3 myelinated endings per square millimeter with a mean diameter of 3.3 ± 0.5μm and an internodal length of 79.1 ± 13.8μm. These findings indicate that Aβ fibers undergo drastic changes in their course from the nerve trunk to the target organ, with repeated branching and consequent tapering and shortening of internodal length. Our work demonstrates that skin biopsy can give information on the status of large myelinated endings as well as unmyelinated sensory and autonomic nerves. Since distal endings are primarily involved in distal axonopathy, skin biopsy can be more suitable than sural nerve biopsy to detect early abnormalities. In addition to diagnostic applications, this technique allows clarification of the mode of termination of Aβ fibers and their relationship with mechanoreceptors, leading to relevant electrophysiological speculations. Ann Neurol 2003